Pengaruh Konten Marketing dan Electronic Word of Mouth (E-WOM) Terhadap Minat Beli Kuliner Melalui Kepercayaan Sebagai Variabel Intervening (Studi Kasus Pada Followers Instagram @bangkafoodbang): Studi Kasus Pada Followers Instagram @bangkafoodbang - Nadia Puspita (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
This study aims to analyze the effect of content marketing and electronic word of mouth (e-wom) on culinary purchase intention through trust as an intervening variable on @bangkafoodbang Instagram followers. The method used in this research is descriptive quantitative with data collection involving 100 respondents of @bangkafoodbang Instagram followers with purposive sampling through distributing questionnaires. This research uses Structural Equation Model-Partial Least Square (SEM-PLS) with SMARTPLS 3.2.9 software. The results showed that marketing content and electronic word of mouth have a positive and significant direct effect on trust. Content marketing and electronic word of mouth also have a direct positive and significant effect on purchase intention. In addition, the indirect test results show that content marketing and electronic word of mouth have a positive and significant effect on purchase intention when mediated by trust.